Checking the Possibility of Implementing Knowledge Management Based on Palovski Model in Iran’s Universities - kohansal jajarm, Javad; Hossein Kayzouri, Amir (International Journal of Engineering and Technology, 2018)
Current study deals with the possibility of knowledge management establishment, and it also considers the different points of view of faculty members and employees in Iranâ€™s university;therefore,we used Palovsky model for dimensions measurement and knowledge management. This study was appliable in nature and descriptive-scaling method was used. Population sample includes 70people of faculty members and 98 employees, thus, accumulated sample by using Morgan chart was 59 and 78 people, respectively. Questionnaires were distributed to the samples by reduction coefficient of 20.Sampling method was classified random sampling. Questionnaire measurement tools were confirmed by 5 management professors the correctness and reliability was tested by Cronbachâ€™s alphaÂ realibility test with the coefficient of 0/95 .In order to verify hypothesis researchers preferred to use sample t-test. According to the results of this study there are possibilities such as, determining knowledge factors, generating knowledge, expanding knowledge, integrating knowledge and transferring knowledge in 3 dimensions with organizational structure in university of Bojnourd. Furthermore, by considering the difference between faculty members and employees point of view about required preparation for knowledge management we used two groups average comparison test, the results showed there is a significant difference between faculty members and employees point of view in all aspects. The result also showed Bojnourd university is ready to establish knowledge management by using Palovsky model.Â